All optical-switching technology in transformer substation network - Jie ZHANG; Peng WU; Sheng WANG; Hai WANG; Tai1 ZHANG; Linghao ZHANG (Dianxin kexue)
The development of network technology promotes the development of the traditional substation to the smart substation,where all devices can exchange the real-time information via the switch in the smart substation.In view of the strict time delay requirement of substation communication service,a full optical switching network architecture for smart substation was proposed,which avoided the operation of optical,electric and optical conversion,and realized the fast and reliable communication between the protection device and the smart terminal as well as the merging unit.